Understanding the Public Health Implications of Prisoner Reentry in California : State-of-the-State Report - Davis, Lois M.; Williams, Malcolm V.; Derose, Kathryn Pitkin, 1963- (RAND Corp., 2011)
Examines the health care needs of newly released California prisoners, the communities most affected by reentry, the capacity of their safety nets, and the experiences of released prisoners, service providers, and families of prisoners.